Study of the impact of IL7R gain-of-function mutation on in vivo leukemogenesis - Soares, Tiago André Dias (2018)
Acute lymphoblastic leukaemia (ALL), the most common childhood malignancy, is characterized by the accumulation of immature lymphoid cells, of either B or T cell origin, in the bone marrow and lymphoid tissues. B cell ALL (B-ALL) is the most common acute leukaemia in children, accounting for 85% of ALL cases, whereas patients with ALL of T cell phenotype (T-ALL) present with high risk. Although ALL treatment has improved in recent years, secondary effects can be severe and around 15-25% of the patients relapse. Hence, better treatments are needed. Interleukin 7 (IL-7) and its receptor (IL-7R; constituted by the IL-7Rα and γc chains) are critical for normal B and T cell development, and IL-7/IL-7R signalling is involved in cell survival, proliferation and differentiation. In Prof. João Barata´s Lab, gain-of-function mutations, present in roughly 10% of T-ALL patients, were previously identified in the exon 6 of IL7R gene, which encodes IL-7Rα. These mutations lead to constitutive activation of IL-7R mediated signalling, without the requirement for the ligand. The aim of this thesis was to study the impact of IL7R gain-of-function mutation in in vivo leukemogenesis. For this purpose, we developed a mouse with conditional expression of the mutated Il7r gene using the CRE/LoxP system and crossed it with CRE lines of interest: CD2CRE; CD4CRE; VavCRE and pLCKCRE. Progeny of these crossings was analysed by performing flow cytometry analysis on blood samples and monitoring leukaemia development. Overall, results show that IL-7R mutational activation has a clear effect in the B cell compartment, while only more subtle changes could be scored in the T cell lineage. The B cell-related alterations affect immature populations in all the animals and an important fraction of these develop B cell leukaemia, which we characterized as B cell precursor ALL. In order to evaluate oncogenic dose effects, we generated animals with homozygous Il7r mutation. Progeny showed a more striking phenotype affecting the B cell compartment when compared to heterozygous mice, as shown by flow cytometry. Western Blot analysis confirmed upregulated signalling in homozygous leukemic cells as compared to heterozygous leukemias and controls.